WORK-LIFE BALANCE AS A MEDIATOR OF THE CORRELATION BETWEEN PSYCHOLOGICAL WELL-BEING AND QUARTER LIFE CRISIS IN EARLY ADULTHOOD IN TERNATE CITY - Febrianti, Fidya Noer Aulia; Ghozali Rusyid Affandi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research is aimed at finding out whether work-life balance is a mediator of connections. psychological well-being and quarter life crisis in early adulthood in the town of Ternate. The population in this study is early adults with a vulnerable age of 18–29 years and are working. Method: This study uses correlational quantitative research methods. The sampling technique used purposive sampling technique and used the Krejcie and Morgan table as a guide to determining the sample which got a sample of 269 early adults with a vulnerable age of 18–29 years and were working. The data collection method uses a psychological scale model, namely a Likert scale adapted from previous research. Data analysis uses path analysis mediation analysis techniques using JASP software. Results: This study found that work-life balance acts as a significant mediator (partial mediation) in the connection between psychological well-being and quarter life crisis with a p value of <0.001, and an estimate value of -0.353. Individuals with good psychological well-being tend to have better work-life balance, which can reduce the level of quarter life crisis that the individual has. Novelty: This study contributes by empirically validating the mediating role of work-life balance in the relationship between psychological well-being and quarter-life crisis in early working adults, particularly within the unique socio-cultural setting of Ternate—an area that has not been widely examined in previous studies.